98 Characteristics and long-term prognosis of patients with European society of cardiology defined heart failure with preserved ejection fraction presenting to secondary care: prospective cohort study. (17th July 2020) - Cole, Charlotte; Lowry, Judith; Paton, Maria; Drozd, Michael; Slater, Thomas; Witte, Klaus; Cubbon, Richard; Kearney, Mark; Gierula, John
Abstract : Introduction: . Heart failure (HF) with preserved ejection fraction (HFpEF) is a growing problem, but its diagnosis and management in routine clinical practice remains difficult. Recent European Society of Cardiology (ESC) guidelines sought to provide a diagnostic framework to identify patients with HFpEF. We aimed to assess the prevalence, characteristics and prognosis of HFpEF patients identified using these guidelines. Methods: We characterised 960 consecutive patients referred from primary care with signs and symptoms of heart failure and elevated NT-proBNP, between 1st May 2012 and 1st May 2013, using the 2016 European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of acute and chronic heart failure. Results: . HFpEF (n=464, 48%) was more common than HF with reduced EF (HFrEF) (n=314, 33%) or neither HFrEF/HFpEF (n=182, 19%). Patients with HFpEF were older, (mean age 83.8 vs. 81.9 years; p<0.01) more frequently female (65% vs. 42%; p<0.01), more likely to have a history of hypertension (64% vs. 49%; p<0.01) and less likely to have a history of myocardial infarction (10% vs. 19%%; p<0.01) than patients with HFrEF. 5-year survival rate was 60.4% (95% confidence interval (CI) 55.9% to 64.9%) in HFpEF, 50.9% (95% CI 45.4% to 56.4%) in HFrEF and 68.1% (95% CI 61.2% to 75%) in patients with neither. Patients with HFpEF had lower age-sex adjusted mortality than with HFrEF (hazard ratio 0.74; 95% CI 0.6 to 0.91). Conclusion: . ESC guided diagnosis of HFpEF can be an important adjunct to management of older patients presenting with symptoms and signs of HF and may be useful in developing new approaches to the treatment of HFpEF. Conflict of Interest: nil